International Security: Current Situation and Ways of Improvement Legal Regulation - Komarnytskyi, Vitalii; Arifkhodzhaieva, Tetiana; Oderii, Oleksiy; Kovalenko, Volodymyr (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2021)
The issue of security is a fundamental aspect in the maintenance of international relations, and such relations cannot be upheld without concrete laws and credible policies underlying the international scene. It is really essential and appropriate in setting strong international security on the international level. With all these in place, ensuring this international security has been a difficult task by actors on the international scene due to the multifacet of the various legal regimes with the diversified policy set up making the objective of international security a laughable phenomenon. The purpose of the article is to determine the characteristic features of the current state of the international security system, based on current situations in a particular region of the world, as well as to establish the relationship between various elements of international security. This great plague attacking international security has been of great questioning too many of the international scene as to what importance will security be necessary when it cannot be respected by those who claim in ensuring international peace and security? In answering this question, it will be appropriate for us in adopting empirical research to examine the various hurdles which can jeopardise international security. From the above outcome experience, one can say with any fear of contraction that the notion of international security is more of procrastination than a plausible redress. It is against this backdrop that we think much still need to be done in ensuring a place occupied by concrete international security, respected by all without violations. Keywords: International Security; Ways of Improvement; International Cooperation; Effective Interaction; Sturdy PolicyKeamanan Internasional: Situasi Saat Ini dan Cara Perbaikan Regulasi Hukum AbstrakIsu keamanan merupakan aspek fundamental dalam pemeliharaan hubungan internasional, dan hubungan semacam itu tidak dapat ditegakkan tanpa undang-undang yang konkrit dan kebijakan yang kredibel yang mendasari kancah internasional. Hal ini sangat penting dan tepat dalam menetapkan keamanan internasional yang kuat di tingkat internasional. Dengan semua ini, memastikan keamanan internasional ini telah menjadi tugas yang sulit oleh para aktor di kancah internasional karena multifaset dari berbagai rezim hukum dengan kebijakan yang beragam membuat tujuan keamanan internasional menjadi fenomena yang menggelikan. Tujuan artikel ini adalah untuk menentukan fitur karakteristik dari keadaan sistem keamanan internasional saat ini, berdasarkan situasi saat ini di wilayah tertentu di dunia, serta untuk menetapkan hubungan antara berbagai elemen keamanan internasional. Wabah besar yang menyerang keamanan internasional ini telah menjadi pertanyaan besar bagi banyak orang di kancah internasional tentang pentingnya keamanan apa yang diperlukan ketika keamanan tidak dapat dihormati oleh mereka yang mengklaim dalam menjamin perdamaian dan keamanan internasional? Dalam menjawab pertanyaan ini, sudah sepantasnya kita mengadopsi penelitian empiris untuk mengkaji berbagai rintangan yang dapat membahayakan keamanan internasional. Dari pengalaman hasil di atas, orang dapat mengatakan dengan ketakutan akan kontraksi bahwa gagasan keamanan internasional lebih merupakan penundaan daripada ganti rugi yang masuk akal. Dengan latar belakang inilah kami pikir masih banyak yang perlu dilakukan untuk memastikan tempat yang ditempati oleh keamanan internasional yang nyata, dihormati oleh semua tanpa pelanggaran.Kata Kunci: keamanan internasional, cara peningkatan, kerjasama internasional, interaksi efektif, kebijakan kokoh Международная безопасность: текущее состояние и пути совершенствования правового регулирования АннотацияЦелью статьи является определение характерных черт современного состояния системы международной безопасности с учетом текущей ситуации в конкретном регионе мира, а также установление взаимосвязи между различными элементами международной безопасности. Государства выдвигают разные, иногда противоречивые предложения по совершенствованию системы международной безопасности, поскольку страны имеют разные возможности для реализации реальных мер по реформированию международной безопасности. Считается, что несколько самых влиятельных стран мира играют основную роль в формировании так называемой «повестки дня» в международной политике, в том числе в сфере безопасности. Их влияние основано на различных сферах общественной жизни. Развитые демократии Западной Европы и Северной Америки оказывают значительное влияние на международно-правовые отношения благодаря своему экономическому, культурному и политическому влиянию. В свою очередь, Россия и Китай в значительной степени повлияли на международную политику через ультиматумы и угрозы из-за своих собственных вооруженных сил, которые по-прежнему остаются если не лучшими, то одними из крупнейших в мире. Особое внимание обращается на тот факт, что Украина в связи с вышеуказанными обстоятельствами должна следовать курсу сближения с развитыми демократиями, чтобы добиться успеха. С учетом проведенного исследования авторами представлены предложения по совершенствованию правового регулирования международной безопасности.Ключевые слова: международная безопасность, защита интересов, международное сотрудничество, противодействие угрозам